Iowa RBA, January 22, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for January 22, 1996. Highlights of the update include sightings of White-winged Crossbills, Long-tailed Duck, Glaucous Gull, Thayer's Gull, Lesser Black-backed Gulls and a Northern Saw-whet Owl. Also included are handwritten notes for the next week's update with sightings of Eurasian Tree Sparrows and a Red-shouldered Hawk. Epson - sheet feed/flatbed